2017
DOI: 10.1177/1471301217739722
|View full text |Cite
|
Sign up to set email alerts
|

The role of participatory music making in supporting people with dementia in hospital environments

Abstract: Background: Improving the quality of care for people with dementia in general

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…It reported a statistically significant difference in levels of pleasure and alertness (The Lawton Observed Emotion Rating Scale; OERS). One case‐control study evaluated this therapy. It reported positive observed effects on relaxation, distraction, engagement, and agitation (ArtsObs; Arts Observational Scale, measuring mood distraction and relaxation) in favour of the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It reported a statistically significant difference in levels of pleasure and alertness (The Lawton Observed Emotion Rating Scale; OERS). One case‐control study evaluated this therapy. It reported positive observed effects on relaxation, distraction, engagement, and agitation (ArtsObs; Arts Observational Scale, measuring mood distraction and relaxation) in favour of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Person‐centred volunteer intervention: One non‐RCT evaluated this intervention. Music therapy: One case‐control study measured the impact of this intervention . Cognitive geriatric unit: One case‐control study measured the impact of this intervention …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary objects can include artistic works and processes, although they have seldom been studied in arts, health and wellbeing contexts. One study of the role of music making in hospital care for people with dementia suggested that music can serve as a boundary object (Daykin et al, 2018b). For example, a conductor's baton stimulated expressive responses and provided a focal point for discussions in which staff and carers reflected on patients' unseen capabilities and needs as well as on their own roles.…”
Section: Social Movements Propagation and Scalementioning
confidence: 99%
“…There are also instances of micro-level resistance to boundary work, such as when a proposed arts activity is rejected on the grounds that it might disrupt the workflow within a clinical setting. In our study of music in acute hospital care for people with dementia, we reported an occasion when a senior clinician entered the room while the music making was in full flow, announcing to a patient that they needed to undertake a minor clinical pro-cedure at that moment (Daykin et al, 2018b). What was interesting about this scenario was the response of care staff, who made strenuous efforts to prevent such incursions in future, giving up time and energy and devising tactics, such as rearranging furniture, to protect the music space.…”
Section: Social Movements Propagation and Scalementioning
confidence: 99%